Can easy chemistry produce complex, diverse, and novel molecules?. Issue 12 (December 2020) - Tomberg, Anna; Boström, Jonas
Graphical abstract: Highlights: An analysis of screening compounds made by different synthetic methods was conducted. The notion that simple reactions cannot produce high quality structures was disproved. Easy chemistry can be a reliable and efficient strategy in medicinal chemistry projects. Innovative chemistry is a necessity for the production of new elaborate building blocks. Statements, such as 'you need to break free from amide-formations to improve molecular properties' and 'novel chemistry leads to novel biology' are frequently encountered in the medicinal chemistry community. To verify whether truth lies in such preconceptions, we investigated whether complex, diverse, and novel molecules can be made by 'easy' chemistry. By analyzing the AstraZeneca screening collection, we conclude that novelty, diversity, and molecular complexity is currently not compromised by the use of the most popular reaction, amide bond formation, mainly because of a recent steady increase in unique amines available. Easy chemistry allows speedy access to a broad chemical space, facilitating progress in projects, and opens the possibility of synthesis automation and new technologies (e.g. DNA-encoded libraries). Teaser: Easy-to-make compounds are often perceived to be inferior compared with molecules obtained through elaborate reaction schemes. This study evaluates in depths whether this perception is true.